Republic of Croatia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper highlights key policy challenges for accelerating growth on a sustainable basis and reducing external and financial vulnerabilities in the Republic of Croatia. A significant reduction in public expenditure would be needed to simultaneously provide room for cutting taxes, boost growth, and lower the budget deficit to help narrow the current account deficit. The analysis finds that Croatian banks are not necessarily passing on the higher risk of foreign exchange-linked loans to unhedged clients by charging higher interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet